Survey of feasibility of a peelable and point-of-use labelling system. Issue 1 (5th August 2013) - Klein, Miriam; Cohen, Henry
Abstract : Objectives: This article describes a collaborative survey undertaken along with clinical practitioners in the UK and in Canada, in the fall of 2008. Its purpose was to identify the risks associated with poor labelling of injectable medicines. Additionally, it seeks to make recommendations to improve patient safety through the use of an innovative labelling system, including 'peelable labels with patient-specific data' and 'point-of-use drug information labels'. Methods: In order to assess the use of these labelling systems, clinicians were surveyed regarding their opinions on 'peelable labels with patient-specific data' and 'point-of-use drug information labels'. Results: Practitioners expressed their support for the use of an innovative labelling system, including 'peelable labels with patient-specific data' and 'point-of-use drug information labels'. Conclusions: Due to the deleterious consequences of medication errors, health systems are always seeking ways to improve and prevent these errors. Innovative drug labelling is one mechanism that can be used to prevent errors. A 'peelable label with patient-specific data' can be affixed to a syringe. This is one proposed mechanism to ensure that patients receive the correct medication and the correct dose. A 'point-of-use drug information label' provides clinicians with drug information at the site of treatment, which may prevent mistakes.